Arms control : - the American Assembly, Columbia University.; American Assembly. (Prentice-Hall, 1961)
Papers prepared for the use of participants in the 19th American Assembly, Arden House, Harriman Campus of Columbia University, May 4-7, 1961, and edited by Louis Henkin. "Final Report of the Nineteenth American Assembly": p. 201-204.